2001
DOI: 10.1053/jlts.2001.25357
|View full text |Cite
|
Sign up to set email alerts
|

Disease recurrence after living liver transplantation for primary biliary cirrhosis: A clinical and histological follow-up study

Abstract: We describe the recurrence of primary biliary cirrhosis (PBC) in recipients of living liver transplants. We are not aware of similar previous reports. Because most donors for living liver transplantation (LLT) are blood relatives with close HLA matches, the recurrence of PBC in transplant recipients might offer additional insights in the pathogenesis of the condition. We studied 6 women (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 31 publications
0
45
1
1
Order By: Relevance
“…Clinically, it can be asymptomatic; total serum bilirubin level and hepatic biochemistry are normal, although serum alkaline phosphatase may be slightly increased. 128,129 Risk factors remain unclear but probably include histocompatibility leukocyte antigen or sex mismatching between donor and recipient 130 and immunosuppression. 131 Dmitrewski et al 131 reported that histologic features characteristic of PBC were found more commonly and earlier after transplantation in patients receiving FK506 than in those given cyclosporine.…”
Section: Recurrent Cholestatic Diseasementioning
confidence: 99%
“…Clinically, it can be asymptomatic; total serum bilirubin level and hepatic biochemistry are normal, although serum alkaline phosphatase may be slightly increased. 128,129 Risk factors remain unclear but probably include histocompatibility leukocyte antigen or sex mismatching between donor and recipient 130 and immunosuppression. 131 Dmitrewski et al 131 reported that histologic features characteristic of PBC were found more commonly and earlier after transplantation in patients receiving FK506 than in those given cyclosporine.…”
Section: Recurrent Cholestatic Diseasementioning
confidence: 99%
“…The number of patients in Hashimoto's study [24] is too small to draw a definitive conclusion. The high rate of recurrence (33% in 2 years) is in sharp contrast with that in an earlier DDLT series.…”
Section: Pbcmentioning
confidence: 96%
“…Hashimoto and colleagues presented the first series of recurrent PBC after LDLT [24] . All patients remained positive for AMA as in DDLT.…”
Section: Pbcmentioning
confidence: 99%
“…[52][53][54][55] Recently, a report has noted the recurrence of primary biliary cirrhosis after living donor liver transplantation. 56 However, because there is considerable histologic overlap between chronic rejection and recurrent PBC, the diagnosis can be challenging. However, patients with chronic rejection usually are distinguishable by having a history of multiple acute rejection episodes, which often differentiates patients with chronic rejection from those with recurrent PBC.…”
Section: S65mentioning
confidence: 99%